PSXIII-14 The impact of estrus intensity on variables associated with fertility in Bos taurus-influenced beef cows. (5th December 2019) - Cooke, Reinaldo F; Oosthuizen, Nicola; Schubach, Kelsey; Brandão, Alice; Filho, Ramiro Oliveira; Colombo, Eduardo; Pohler, Ky
Abstract: To evaluate the impact of estrus expression and intensity on parameters associated with reproductive performance, 219 lactating, multiparous Bos taurus-influenced beef cows were enrolled in this study. Cows were exposed to an estrus synchronization protocol, where they received a 100-µg injection of GnRH and a CIDR insert on d -10, a 25-mg injection of PGF2a at CIDR removal on d -3, and an injection of GnRH 60–66 h following CIDR removal at fixed-time AI (TAI; d 0). Cows were fitted with a pedometer behind their right shoulder on d -10, and an estrus detection patch was applied to their tail-head on d -3. Estrus expression was defined as removal of > 50% of the rub-off coating from the patch on d 0. Net physical activity during estrus was calculated by subtracting daily activity during the non-estrus period (d -10 to -3) from activity during the expected estrus period (d -3 to 0). Cows were classified into 3 groups: cows that did not express estrus (NOESTR; n = 119), cows that expressed estrus with net physical activity greater than the median (HIESTR; n = 50), and the remaining cows (LWESTR; n = 50). Ultrasonography was performed on d -3, 0, and 7 to determine the presence and size of ovarian structures. Pregnancy diagnosis was performed 29 d after TAI. Net physical activity was greater in HIESTR compared to both LWESTR and NOESTR (P < 0.01). Dominant follicle size was greater in HIESTR compared to both LWESTR and NOESTR (P < 0.01). Furthermore, HIESTR had greater corpus luteum volume on d 7 than LWESTR and NOESTR (P < 0.01). Pregnancy rates to AI (PR/AI) were greater in HIESTR and LWESTR compared to NOESTR (P < 0.01). In conclusion, cows that expressed estrus at a greater intensity had improved ovarian dynamics. Additionally, cows that exhibited estrus had greater PR/AI compared to non-estrual cows.